2020
DOI: 10.1039/d0ra00933d
|View full text |Cite
|
Sign up to set email alerts
|

Cu(i) substituted wurtzite ZnO: a novel room temperature lead free ferroelectric and high-κ giant dielectric

Abstract: Cu+ ion substituted ZnO, Zn1−xCuxO1−δ have shown high dielectric constant (∼6300) at 600 °C at 100 kHz frequency and ferroelectricity at room temperature than for bulk Zn0.95Cu0.05O1−δ samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Also, the peaks except for ZnO and Fe3O4 compound (CuO and Cu2O) were not observed, suggesting that the substitution of Cu in ZnO lattice was not altering the wurtzite structure of ZnO. It is due to the ionic radius of Cu 2+ (0.73 Å) is slightly the same as the ionic radius of Zn 2+ (0.74 Å) [21]. It confirmed that the Fe3O4/ZnO-Cu photocatalyst had been successfully synthesized.…”
Section: Resultsmentioning
confidence: 68%
“…Also, the peaks except for ZnO and Fe3O4 compound (CuO and Cu2O) were not observed, suggesting that the substitution of Cu in ZnO lattice was not altering the wurtzite structure of ZnO. It is due to the ionic radius of Cu 2+ (0.73 Å) is slightly the same as the ionic radius of Zn 2+ (0.74 Å) [21]. It confirmed that the Fe3O4/ZnO-Cu photocatalyst had been successfully synthesized.…”
Section: Resultsmentioning
confidence: 68%
“…Up to 8 %, Cu + ion substitution on Zn 2 + sites in the ZnO lattice was achieved by careful selection of raw material and adaptation of a lowtemperature sol-gel synthesis route for the preparation of bulk material and Cu + ion substitution on Zn 2 + sites in ZnO lattice not only resulted in net polarization but also open the path for strong polarization between O2p and filled d 10 Zn/Cu 4p orbital in tetrahedral coordination resulting high k dielectricity in the material. [41] The dielectric constant (ɛ r ') of ZnO is approx. 450 at 1000 Hz frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, an even rarer phenomenon called the electric auxetic effect 7) (longitudinal and transverse piezoelectric coefficients are of the same sign) has been predicted. Wurtzite materials as promising piezoelectrics possess the superb features of non-toxicity 9,10) and high thermal stability, [11][12][13] and have found widespread applications in piezoelectric nanogenerators, 14) strain sensors, [15][16][17] and energy harvesting devices. 18) Attempts have been made to obtain wurtzite semiconductors with desired piezoelectric responses via alloying [19][20][21][22][23] and strain engineering.…”
mentioning
confidence: 99%